Propuesta de mejora de la efectividad global de los equipos basado en la aplicación de herramientas Lean Manufacturing y gestión de proveedores en una empresa dedicada a la fabricación y comercialización de concreto premezclado - Aguirre Huaman, Jose Carlo (2022)
The present improvement study is developed in the private company Lidermix S.A.C. with an industrial plant in the district of Lurigancho-Chosica, where the manufacture and commercialization of ready-mix concrete is carried out. The authors make an analysis to the flow of the productive process with the purpose of raising possible proposals of improvement based on the results obtained according to the evaluation of the diagnosis made with the engineering tools and with the collection of data in the visits to the industrial plant and information given by the people in charge of the production area. In addition, they use quality reference and bibliographic data consulted in the database in which the Universidad de Lima is affiliated, such as scientific articles, journals and electronic books, in order to have a strong foundation to elaborate research of a purely educational nature. The proposals for improvement are aimed at improving the availability of machines and equipment involved in production for the benefit of the use of resources needed by the company. The cost of implementing both improvement proposals amount to a total of S/ 460 653,00 with an internal economic and financial rate of return of 25,88% and 30,62%, respectively.